STUDENTS’ CRITICAL THINKING ABILITY IN ENGLISH TEACHING AND LEARNING - Tini Mogea (Lembaga Pengembangan Kinerja Dosen, 2022)
The purpose of this study was to discover how students' critical thinking skills developed during the classroom learning process. This research was conducted at SMA Negeri 1 Ratahan, and the sample is the first-year students, which was made up of 35 students. The instruments used in collecting data are observation techniques. The data were analyzed qualitatively. 1) The concept of purpose was present in Meetings 2, 3, 4, and 5. It is shown that when students reason, they reason to achieve some objective, to satisfy some desire, or to fulfill some need. 2) The concept of